I'm really sorry about how messy this looks; I'm still trying to figure out how to use the math notation thing.
Anyway, the problem is:
Given A0=1 and An+1=(3*An)+1, find the definition for An
I just have no idea how to go about doing this. You don't have to give the answer, just any sort of hint as to procedure would be great. Thank you!
So I think I'm getting An=Sum from i=1 to n of
Originally Posted by CaptainBlack
That makes sense, because you multiply each previous term by 3, so there must be an exponent in there... haha, i think it's coming together in my head. Thank you!
Close. But actually the sum will be from i = 0: .
Originally Posted by sfitz